Portwine stain with nodular thickening and intraoral hemangioma - Ankita Bohra; Sumit Bhateja; Geetika Arora (Wolters Kluwer Medknow Publications, 2016)
Vascular anomalies are a heterogeneous group of congenital blood vessel disorders more typically referred to as "birthmarks." They are further categorized into vascular tumors and malformations, which are again subdivided into various types based on specific morphology, pathophysiology, clinical behavior and management of particular entity. Hemangiomas are the most common vascular tumors. Lymphatic, capillary, venous and arteriovenous malformations are the main subdivisions under the heading of vascular malformations. This paper discusses a case of co-occurrence of portwine stain with intraoral hemangioma.